Models of viral capsid symmetry as a driver of discovery in virology and nanotechnology. (3rd February 2021) - Dechant, Pierre-Philippe; Twarock, Reidun
Abstract : Viruses are prominent examples of symmetry in biology. A better understanding of symmetry and symmetry breaking in virus structure via mathematical modelling opens up novel perspectives on how viruses form, evolve and infect their hosts. In particular, mathematical models of viral symmetry pave the way to novel forms of antiviral therapy and the exploitation of viral protein containers in bio-nanotechnology.